2020
DOI: 10.1016/j.rasd.2020.101645
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Longitudinal Sensory Subtypes in Typical Development and Autism Spectrum Development Using Growth Mixture Modelling

Abstract: Background-Prior longitudinal investigations of trajectories of sensory features in Autism Spectrum Development (ASD) have not explored heterogeneity. The present study explores initial levels and trajectories of sensory features in ASD as well as, for comparison, typical development.Method-Growth mixture modelling was used to explore classes of autistic and typicallydeveloping participants based on caregiver-reported total sensory behaviours on the Short Sensory Profile (SSP) at two time points, when children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 51 publications
6
22
3
1
Order By: Relevance
“…Cognitive functioning, adaptive behavior, age, and sex did not impact SAND or ADOS-2 scores, both of which capture direct observation of symptoms. Interestingly, results from the SAND suggest a preservation of sensory symptoms with age, which is consistent with recent studies in individuals with idiopathic ASD demonstrating stability of sensory symptoms throughout early and middle childhood [44][45][46]. IQ/DQ, adaptive behavior, and age were correlated with several SSP scales, suggesting that the higher the cognitive or adaptive level and older the individual, the fewer abnormal sensory responses parents reported.…”
Section: Discussionsupporting
confidence: 88%
“…Cognitive functioning, adaptive behavior, age, and sex did not impact SAND or ADOS-2 scores, both of which capture direct observation of symptoms. Interestingly, results from the SAND suggest a preservation of sensory symptoms with age, which is consistent with recent studies in individuals with idiopathic ASD demonstrating stability of sensory symptoms throughout early and middle childhood [44][45][46]. IQ/DQ, adaptive behavior, and age were correlated with several SSP scales, suggesting that the higher the cognitive or adaptive level and older the individual, the fewer abnormal sensory responses parents reported.…”
Section: Discussionsupporting
confidence: 88%
“…The significance and meaningfulness of these subgroups is emphasized by findings that cognitive ability, anxiety, sleep quality, and auditory event-related potential amplitudes differed across autistic participants assigned to separate classes. Notably, allowing levels of the latent factor to vary over time did not appear to improve model fit, in contrast to results obtained by Dwyer et al (2020a) in the same sample. This may reflect the very limited number of participants with atypical trajectories observed by Dwyer et al, coupled with the greater complexity of the factor mixture model used in the present study.…”
Section: Discussioncontrasting
confidence: 88%
“…Relatively few longitudinal studies have explored sensory subgroups in ASD (cf. Ausderau et al, 2014Ausderau et al, , 2016Dwyer et al, 2020a). The factor mixture modelling approach that is used in the present longitudinal study allows subgroups to vary in levels of latent variables over time.…”
Section: Heterogeneity Of Sensory Featuresmentioning
confidence: 99%
“…With regards to development over time, the two studies showed that overall there was a decrease in sensory processing difficulties. This finding is different from children with autism for whom it has been found that profiles remained stable or sensory difficulties increased in a small sample of participants (Dwyer et al, 2020;Perez Repetto et al, 2017). In addition, there were differences between the factors: whilst visual processing difficulties decreased, vestibular processing difficulties increased.…”
Section: Discussioncontrasting
confidence: 76%